Finger Length Ratios in Serbian Transsexuals - Svetlana Vujović; Srdjan Popović; Ljiljana Mrvošević Marojević; Miomira Ivović; Milina Tančić-Gajić; Miloš Stojanović; Ljiljana V. Marina; Marija Barać; Branko Barać; Milena Kovačević; Dragana Duišin; Jasmina Barišić; et al. (The Scientific World Journal)
Atypical prenatal hormone exposure could be a factor in the development of transsexualism. There is evidence that the 2nd and 4th digit ratio (2D : 4D) associates negatively with prenatal testosterone and positively with estrogens. The aim was to assess the difference in 2D : 4D between female to male transsexuals (FMT) and male to female transsexuals (MFT) and controls. We examined 42 MFT, 38 FMT, and 45 control males and 48 control females. Precise measurements were made by X-rays at the ventral surface of both hands from the basal crease of the digit to the tip using vernier calliper. Control male and female patients had larger 2D : 4D of the right hand when compared to the left hand. Control male’s left hand ratio was lower than in control female’s left hand. There was no difference in 2D : 4D between MFT and control males. MFT showed similar 2D : 4D of the right hand with control women indicating possible influencing factor in embryogenesis and consequently finger length changes. FMT showed the lowest 2D : 4D of the left hand when compared to the control males and females. Results of our study go in favour of the biological aetiology of transsexualism.